MEMAHAMI MAKNA BATIN KITAB SUCI - Rohmana, Jajang A (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2015)
This article aims to analyze the esoteric interpretation of the Qur'an written in Sundanese. The object of the study is theQuranul Adhimiof Haji Hasan Mustapa (1852-1930). Through the analysis of hermeneutics, this study shows that the local exegesis can not be assumed that it has the same character as the Malay-Indonesian exegesis. Indeed, it shows local creativity born out of the diversity of cultural backgrounds. It also shows the process of the dialogue between Sufism and the inner of Sundanese people in the frame of Qur'anic exegesis. This can be proven in three ways: the interpretation centered on the inner meaning, the use of natural metaphors, and the nuances of Sundanese literature. The significance of Mustapa 'sexegesis lies in the process of indigenization of the Qur'an (Islam) to the characteristics of the local Islamic tradition through the work of Quranic exegesis. This work clearly indicates the local creativity in responding to the intellectual tradition of Sufism, especially the Sufi interpretation. Not only through metrical poetry, he also interprets mystical experiences through theexegesis. Key words: exegesis, Quran, Sufism, Inner, Sundanese